1990
DOI: 10.1111/j.1365-3040.1990.tb01302.x
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll fluorescence measured using the Fraunhofer line‐depth principle and relationship to photosynthetic rate in the field

Abstract: Abstract. A field study was conducted to determine the relationship of solar‐excited chlorophyll a fluorescence to net CO2 assimilation rate in attached leaves. The Fraunhofer line‐depth principle was used to measure fluorescence at 656.3 nm wavelength while leaves remained exposed to full sunlight and normal atmospheric pressures of CO2 and O2. Fluorescence induction kinetics were observed when leaves were exposed to sunlight after 10 min in darkness. Subsequently, fluorescence varied inversely with assimilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 18 publications
0
28
0
1
Order By: Relevance
“…Initial studies using the PFS on agricultural crops have shown that CF emission may provide a more timely indicator of plant stress than chlorophyll content. Earlier studies using near-contact methods showed the efficacy of the RlFR ratio in detecting ozone effects in Pinus strobus (Theisen et aI., 1994). Carter et al (1990 used the Fraunhofer line-depth principle to relate CF to photosynthetic rate in Pinus taeda and Liquidambar styraeiflua (distance of 0.4 m between sensor and foliage), and found an inverse relationship between CF at 656.3 nm and C02 assimilation rate.…”
Section: Passive Methodsmentioning
confidence: 97%
“…Initial studies using the PFS on agricultural crops have shown that CF emission may provide a more timely indicator of plant stress than chlorophyll content. Earlier studies using near-contact methods showed the efficacy of the RlFR ratio in detecting ozone effects in Pinus strobus (Theisen et aI., 1994). Carter et al (1990 used the Fraunhofer line-depth principle to relate CF to photosynthetic rate in Pinus taeda and Liquidambar styraeiflua (distance of 0.4 m between sensor and foliage), and found an inverse relationship between CF at 656.3 nm and C02 assimilation rate.…”
Section: Passive Methodsmentioning
confidence: 97%
“…For years, studies have noted a close association between solar-induced chlorophyll fluorescence (SIF) and photosynthetic activity (Carter et al, 1990). Recent studies, mostly from spaceborne platforms, have demonstrated a strong link between GPP and SIF (Frankenberg et al, 2011;Joiner et al, 2011Joiner et al, , 2014.…”
Section: Solar-induced Fluorescencementioning
confidence: 99%
“…Since changes in SIF red and SIF FR were found to influence NDVI values, with a high SIF corresponding to increases in NDVI, the red reference wavelength was shifted to 647 nm and the FR reference wavelength was taken at 868 nm to minimise this influence. Retrieval of SIF was performed using the Fraunhofer Line Discriminator (FLD) [33] and the 3FLD [34] methodologies within both the O 2 -A and O 2 -B absorption spectral regions. Under low levels of leaf irradiance (<150 µmol photons·m −2 ·s −1 ), the 3FLD SIF retrieval occasionally resulted in negative estimates of SIF.…”
Section: Retrieval Of Reflectance Indices and Solar Induced Fluorescencementioning
confidence: 99%